PENGARUH DIMENSI KUALITAS AUDIT TERHADAP KEPUASAAN AUDITEE: (Studi Empiris Pada Lingkup Pemerintah Daerah Provinsi Maluku) - Dirk Berly Tehuayo (P3M Politeknik Negeri Ambon, 2022)
This study aims to examine and analyze empirically the influence of audit quality dimensions, which includes reputation, capability, independence, expertise, experience, responsive attitude and auditor empathy for auditee satisfaction. This research was conducted on Maluku provincial government officials from 20 SKPD who are regional financial managers in each SKPD (Head of Sub Division / financial sector and PPKD staff, as well as SKPD Treasurer).Data collection techniques used were survey techniques using questionnaires. Data analysis uses multiple linear regression.The results of the research show that the auditor's reputation, capability, independence, expertise and experience have a positive and significant influence on the auditee's position. While responsive attitude, and auditor's empathy attitude does not significantly influence auditee satisfaction..Keywords: Audit quality, reputation, capability, independence, expertise, experience, responsiveness, empathy attitude, auditee satisfaction